Strong signal increase in STED fluorescence microscopy by imaging regions of subdiffraction extent - Göttfert, Fabian; Hell, Stefan (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Photobleaching remains a limiting factor in superresolution fluorescence microscopy. This is particularly true for stimulated emission depletion (STED) and reversible saturable/switchable optical fluorescence transitions (RESOLFT) microscopy, where adjacent fluorescent molecules are distinguished by sequentially turning them off (or on) using a pattern of light formed as a doughnut or a standing wave. In sample regions where the pattern intensity reaches or exceeds a certain threshold, the molecules are essentially off (or on), whereas in areas where the intensity is lower, that is, around the intensity minima, the molecules remain in the initial state. Unfortunately, the creation of on/off state differences on subdiffraction scales requires the maxima of the intensity pattern to exceed the threshold intensity by a large factor that scales with the resolution. Hence, when recording an image by scanning the pattern across the sample, each molecule in the sample is repeatedly exposed to the maxima, which exacerbates bleaching. Here, we introduce MINFIELD, a strategy for fundamentally reducing bleaching in STED/RESOLFT nanoscopy through restricting the scanning to subdiffraction-sized regions. By safeguarding the molecules from the intensity of the maxima and exposing them only to the lower intensities (around the minima) needed for the off-switching (on-switching), MINFIELD largely avoids detrimental transitions to higher molecular states. A bleaching reduction by up to 100-fold is demonstrated. Recording nanobody-labeled nuclear pore complexes in Xenopus laevis cells showed that MINFIELD-STED microscopy resolved details separated by <25 nm where conventional scanning failed to acquire sufficient signal.
Published first February 13, 2017
Gesehen am 25.10.2018